Al-fikr al-Hdāthi: Muḥammad Shaḥrur wa Taqsimuhu li Ayāt al-Qurʾān al-Karim fi Kitābhi "al-Kitāb wa al-Qurʾān" Namudhjan - Malik, Mohammad Manzoor; Khan, Musaddiq Majid (Faculty of Islamic Revealed Knowledge and hHman Sciences (IRKHS), International Islamic University Malaysia, 2011)
Many writers who appeared in our time undertook the study of the texts of the Quran and Sunnah and named it as a “modernist reading”. They claimed that it is in the way to defend Islam and to rescue it from the narrow corner in which Muslims have placed it. They count themselves as the saviours of Islamic thought by rescuing it from pedestrians of the European civilization and traditional Islamic thought, when in fact they had demolished the foundations of the religion and the verses of the book of God. Among these writers is Muhammad Shahrour, as he divided the verses of the Quran into three types and denied mericulous nature of the Quran under one of these types. The research sheds light on the idea of modernity and criticises the division of the Quranic verses by Shahrour and shows its defects.